Utilization of Red Nonionogenic Tenside Labeling, Isoelectric Focusing, and Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry in the Identification of Uropathogens in the Presence of a High Level of Albumin - Horká, Marie; Šalplachta, Jiří; Růžička, Filip; Šlais, Karel (ACS infectious diseases, 2019)
Cellulose-based preparative isoelectric focusing was used for preseparation and concentration of uropathogens Staphylococcus aureus, Escherichia coli, Enterococcus faecalis, Staphylococcus epidermidis, Candida albicans, and Candida parapsilosis in a urine sample containing a high concentration of human serum albumin. For the visibility of the colorless microbial zones in the separation medium, the microbial cells were labeled with red nonionogenic tenside (1-[[4-(phenylazo)phenyl]azo]-2-hydroxy-3-naphthoic acid polyethylene glycol ester, PAPAN). A very short incubation time, about 2 min, was sufficient for the adsorption of 0.001% (w/v) PAPAN onto the cell surface at the optimized conditions. As low as 103 cells of E. coli (pI 4.6) resuspended in 100 μL of urine sample and spiked with 0.1 mg mL-1 of human serum albumin (pI 4.8) were successfully preseparated and concentrated using this method. Because the pI values of the labeled microorganisms remained unchanged, the focused red zones of microbial cells were collected from the separation media and further analyzed by either capillary isoelectric focusing or matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The viability of the cells extracted from the collected zones was also confirmed. The proposed method provides reliable, relatively fast, and cost-effective identification of uropathogens in urine specimens with a high level of albumin.
Keywords: Fungi; Isoelectric Focusing; high level of albumin; uropathogens; red nonionogenic tenside; Bacteria; houby; lidský sérový albumin; Surface-Active Agents; Urinary Tract Infections; lidé; matrix-assisted laser desorption/ionization time-of-flight mass spectrometry; infekce močového ústrojí; povrchově aktivní látky; Humans; barvení a značení; spektrometrie hmotnostní - ionizace laserem za účasti matrice; preconcentration and preseparation; Staining and Labeling; isoelectric focusing; Serum Albumin, Human; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; isoelektrická fokusace